The Role of Doctors in Drug Administration and the Execution of Penal Death - Tongat Tongat; Ratri Novita Erdianti; Said Noor Prasetyo; Nu’man Aunuh; Yaris Adhial Fajrin; Wafda Vivid Izziyana (Institute of Medico-legal Publications Pvt Ltd, 2021)
Although until now Indonesia still applies capital punishment, efforts to limit its application are still beingmade, including improving the procedures for its implementation. One way to ensure that the execution ofthe death penalty is still carried out with respect for life is to involve doctors in treatment and the executionof the death penalty. In addition, in the reform of Indonesian criminal law (Draft KUHP), a policy forpostponing death penalty has been formulated. Those sentenced to death are given the opportunity to improvethemselves for a certain time (10 years). If within the grace period the convict can show improvement inhimself, then the death penalty need not be carried out and replaced with deprivation of liberty.